The Effect of Combination Pranayama Yoga and Endurance Training Exercise on Peak Expiratory Flow (PEF) in Adult Asthmatic Patients - Akbar Nur; Kusnanto Kusnanto; Muhammad Amin; Muhammad Sajidin; Ninuk Dian Kurniawati; Arief Bakhtiar (Jurnal Keperawatan Padjadjaran, 2020)
Pranayama Yoga can help improve breathing, and improve calm and also relieve stress. Endurance training can increase lung capacity, improve fitness, and relax the body. However, the combination of pranayama yoga and endurance exercises has never been done in asthma patients. The purpose of this study was to analyze the combination of pranayama yoga exercises and endurance exercises for Increased Peak Forced Expiration Flow. The design of this study was Quasy Experiment with a pretest-posttest control group design, the location of the study was in the pulmonary clinic of Universitas Airlangga Hospital and Haji General Hospital in Surabaya, East java. Respondents were selected by purposive sampling techniques in accordance with inclusion criteria with a total of 72 respondents. Peak Expiration Flow is measured from forced vital capacity or The peak expiratory flow (PEF) is the maximum flow obtained within the first 200 milliseconds of a forced expiratory maneuver after inhalation to total lung capacity (TLC). The intervention group was given a combination exercise by doing pranayama yoga and endurance exercise for 6 weeks, 2x per week, 51 minutes for each training session. Pranayama yoga combination exercises and endurance exercise using trainer instructors and modules. FPEF and asthma control were measured every week for 6 weeks. The results showed a significant difference in the level of FPEF and asthma control before and after 6 weeks of interventions combination of pranayama yoga and endurance exercise in the intervention group obtained significance values (p <0.05) with p = 0.000 and asthma control in the intervention group (p <0, 05) with p = 0.000 the results of the research shows that by practicing pranayama yoga and endurance exercise can improve FPEF and asthma control. Pranayama yoga and endurance exercise can be used as an complementary therapy in supporting pharmacological therapy to improve FPEF and control asthma.